Cervical Cancer A Global Public Health Treatise - Rajkumar, Rajamanickam (IntechOpen, 2021)
Although it is preventable and curable, cervical cancer is the fourth most common form of cancer among women worldwide. As such, the World Health Organization adopted a Cervical Cancer Elimination Initiative, which aims to eliminate cervical cancer by 2030. This book discusses plans, programs, strategies, solutions, research, and revolutions necessary to achieve this goal. Chapters cover such topics as epidemiology, HPV vaccination, screening and treatment, and prevention and control.